Static Balance Differences in Adolescent with Obesity Before and After The Medial Arch Support Usage - Nur Rachmat; Dwi Setyawan; Annisa Eka Septiani; Esti Novi Andyarini (State Islamic University of Sunan Ampel, 2018)
Obesity is a global epidemic and has become a health issue that must be addressed immediately.The purpose of this study was to analyze the Effect of the Medial Arch Support to a Static Balance in adolescent with obesity in SMA N 1 Tangen. This research was using quasi experimental method with a single group pre test and post test designed. Fifteen students were selected as research subject based on inclution and exclution criterias. The subjects were given an explanation of the purpose of this study and voluntarily participated by signing informed consent. The pre test (before using medial arch cupport) and post test (after using medial arch support) stages was conducted by using standing stork test. Data was analyzed using wilcoxon test hypotheses. The result of the study showed a significant influence on the medial arch support usage to increase the static balance in adolescent with obesity in SMA N 1 Tangen. It is showed by probability value p=0.029 for the right leg and p=0.023 for the left leg.